Development and psychometric evaluation of the need assessment tool for women survivors of rape: Protocol for a mixed methods study - Leila Asadi; Mahnaz Noroozi; Hajar Salimi; Fardin Mardani; Sara Jambarsang (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Rape can lead to various physical and psychological consequences. Thus, survivors should receive immediate interventions and need-based care. The present study aims to design and psychometric evaluation of needs in women survivors of rape. MATERIALS AND METHODS: This mixed methods study is conducted using a sequential exploratory approach. In the first phase, the participants (women survivors of rape and healthcare providers) are selected through purposive sampling in Isfahan. Data are collected through in-depth semi-structured interviews and field notes and are analyzed using conventional qualitative content analysis. The draft of the questionnaire is prepared based on the findings of the qualitative phase and literature review. Then, the face validity, content validity, and reliability of the questionnaire are assessed. Construct validity is assessed using the exploratory factor analysis through a descriptive cross-sectional study on women survivors of rape in the quantitative phase. Using a convenience sampling method, the data are collected in the research environment and analyzed via descriptive and inferential statistical methods. Cronbach's alpha coefficient is used to assess the internal correlation of the questionnaire. CONCLUSION: The valid and reliable questionnaire that is developed in this study can be used by planners to provide services and care according to the needs of women survivors of rape.